STRATEGI PEMELIHARAAN SARANA PRASARANA DALAM MENCIPTAKAN LINGKUNGAN BELAJAR YANG NYAMAN DI SDN 006/IX SUNGAI DUREN - Hariri, Humairah Al; Khotimah, Husnul; Summiyani, Summiyani; Putri, Adiva Cholila; Selpi, Selpi; Zabadiah, Julia Aurel; shodiq, Muhammad shodiq; Akbar, Maulana (STKIP Pesisir Selatan, 2026)
Islamic boarding schools are Islamic educational institutions that play an important role in character building and improving the quality of human resources. Muhammadiyah Curup Islamic Boarding School, as one of the modern Islamic boarding schools, faces challenges in managing the elements of the boarding school to remain relevant and of high quality. This study aims to describe strategies for optimizing pesantren elements, including leadership, curriculum, boarding school system, character building of santri (students), and utilization of the mosque. This study uses a qualitative approach with methods of interviews, observation, and documentation. The results show that the integration of organizational values, curriculum renewal, and an accountability-based managerial system can improve the quality of student education. A value-based coaching approach and communicative relationships between educators and students also contribute to the program's success. The conclusion of this study shows that the systematic optimization of pesantren elements can improve the quality of education and support the transformation of modern pesantren with character.